Tourism Suitability and Carrying Capacity Assessment for Whale Shark Ecotourism in Botubarani, Gorontalo Bay - Sri Fitriani Monoarfa; Fredinan Yulianda; Taryono Taryono (Tomini Journal of Aquatic Science, 2025)
Whale shark (Rhincodon typus) tourism has emerged as a potential marine-based economic activity in several regions of Indonesia, including Botubarani Village, Gorontalo Province. However, sustainable development of this tourism depends on understanding the suitability of the area and its carrying capacity to avoid ecological disturbances. This study aims to determine the resource potential through area suitability and tourism carrying capacity analysis for whale shark tourism in the waters of Botubarani Village. Field research was conducted from May to July 2019, using both primary and secondary data obtained from field observations, transmitter–receiver monitoring, and relevant institutional reports. The suitability analysis was performed using five ecological parameters—frequency and duration of appearance, water transparency, visibility, and current velocity, while the tourism carrying capacity was calculated based on visitor interaction regulations and available observation time. The results showed that the whale shark tourism area, covering approximately 65 hectares, falls into two categories: suitable (75.15%) and conditionally suitable (24.85%), indicating favorable environmental conditions for conservation-based tourism. The average water transparency was 10.76 m, visibility 8.9 m, and current velocity 0.0836 m/s, which are safe and comfortable for marine tourism activities. The tourism carrying capacity (TCC) was estimated at 24 visitors per day, equivalent to 528 visitors per month and 1,560 visitors during peak months (May–July), which remains below the optimal capacity. The findings suggest that whale shark tourism in Botubarani has high potential to be developed sustainably through regulated visitor management, conservation fees, and adherence to interaction guidelines. This study provides a scientific foundation for local authorities to design management strategies and spatial policies that balance ecological preservation with community welfare.